ANALISIS BENTUK POLITICAL PARTICIPATORY CULTURE FANBASE ANIES BASWEDAN - Arrafii, Aqil; Syammas, Ilyasa; Rumahorbo, Yuslin Ridho Julio (Airlangga University, 2025)
This study examines the phenomenon of the